2020
DOI: 10.1002/ar.24531
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of human soft palate muscles

Abstract: Our objective was to determine the branching and distribution of the motor nerves supplying the human soft palate muscles. Six adult specimens of the soft palate in continuity with the pharynx, larynx, and tongue were processed with Sihler's stain, a technique that can render large specimens transparent while counterstaining their nerves. The cranial nerves were identified and dissection followed their branches as they divided into smaller divisions toward their terminations in individual muscles. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
0
21
0
1
Order By: Relevance
“…30,31 Our recent study showed that human MU muscle is innervated by the LPN only. 2 This novel finding challenges the current and prevailing view that the LPN is a sensory nerve that innervates the palatal mucosa and palatine glandular tissue. 1 MU muscle is regarded as a velar elevator, stiffness modifier, and extensor.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…30,31 Our recent study showed that human MU muscle is innervated by the LPN only. 2 This novel finding challenges the current and prevailing view that the LPN is a sensory nerve that innervates the palatal mucosa and palatine glandular tissue. 1 MU muscle is regarded as a velar elevator, stiffness modifier, and extensor.…”
Section: Discussionmentioning
confidence: 91%
“…22 Our study showed that the human LVP receives dural innervation from both the pharyngeal branch of the X nerve and LPN. 2 LVP is the primary muscle for velar elevation and velopharyngeal closure for speech production 23,24 and swallowing. 25 During swallowing and speech, velopharyngeal closure is achieved by the velum, lateral and posterior pharyngeal walls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations